Fundamentals of data communication networks - Ibe, Oliver C. [ (Oliver Chukwudi)] , 1947-
Fundamentals of Data Communication Networks is a must-readfor advanced undergraduates and graduate students in electrical and computer engineering. It is also a valuableworking resource for researchers, electrical engineers, and technical professionals